2003
DOI: 10.1091/mbc.e02-08-0468
|View full text |Cite
|
Sign up to set email alerts
|

KDEL and KKXX Retrieval Signals Appended to the Same Reporter Protein Determine Different Trafficking between Endoplasmic Reticulum, Intermediate Compartment, and Golgi Complex

Abstract: Many endoplasmic reticulum (ER) proteins maintain their residence by dynamic retrieval from downstream compartments of the secretory pathway. In previous work we compared the retrieval process mediated by the two signals, KKMP and KDEL, by appending them to the same neutral reporter protein, CD8, and found that the two signals determine a different steady-state localization of the reporter. CD8-K (the KDEL-bearing form) was restricted mainly to the ER, whereas CD8-E19 (the KKMP-bearing form) was distributed al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
80
0
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 99 publications
(85 citation statements)
references
References 58 publications
4
80
0
1
Order By: Relevance
“…As expected, a perinuclear subpopulation of the CD8.NefNL4-3 chimera localized partially to the TGN ( were not detected at ER structures (data not shown). This pattern is reminiscent of that described in a recent report, where a CD8.E19 chimera that contained the KKMP motif at the C terminus was localized mostly to the intermediate compartment and the TGN (27,45). We conclude that the mutant CD8.NefKKXX and the CD8.NefF12 chimeras both localized to the intermediate compartment in cells.…”
Section: Resultssupporting
confidence: 87%
“…As expected, a perinuclear subpopulation of the CD8.NefNL4-3 chimera localized partially to the TGN ( were not detected at ER structures (data not shown). This pattern is reminiscent of that described in a recent report, where a CD8.E19 chimera that contained the KKMP motif at the C terminus was localized mostly to the intermediate compartment and the TGN (27,45). We conclude that the mutant CD8.NefKKXX and the CD8.NefF12 chimeras both localized to the intermediate compartment in cells.…”
Section: Resultssupporting
confidence: 87%
“…However, the colocalization of these molecules with calnexin suggests that they may have been misfolded or may have undergone retrograde transport to the ER from the trans-Golgi compartment. 19,20 Some colocalization of chains with cis-Golgi markers was observed, but only in patients with higher levels of surface IgM expression, consistent with this possibility (data not shown). Nevertheless, the possible involvement of the N-linked glycosylation of both and CD79a chains in defective surface expression of IgM in CLL is of particular interest.…”
Section: Discussionsupporting
confidence: 73%
“…To perform the PLA analysis we started with human hepatoma Huh-7 cells. These cells are larger and flatter than HEK293 cells, exhibit a well-defined and extended ER when observed with light microscopy (D'Agostino et al, 2011; Stornaiuolo et al, 2003), and do not express a detectable level of CRYAB (data not shown). Next, we generated a PLA-suitable mouse polyclonal antibody, specific for the cytosolic C-terminal tail of Fz4-FEVR.…”
Section: Cryab Interacts With Wild-type and Mutant Fz4 Formsmentioning
confidence: 80%